Sindrom Raynaud: Laporan Kasus - Sary, Sanny Kusuma; Adiyanti, Sri Suryo (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Raynaud’s phenomenon is a condition characterized by sudden discoloration of the skin on the fingers caused by vasospasm. It can occur either as a primary condition or secondary to other diseases, such as Sjogren’s syndrome. Laboratory tests play an essential role in diagnosing and treating Raynaud’s syndrome. Case Report: A 38-year-old woman with clinical Raynaud’s syndrome underwent Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) examinations, which resulted in prolonged values. The patient complained of pain and a black wound on the tips of the 2nd and 3rd fingers of the left hand. The patient was checked for PT, APTT, lupus anticoagulant (LA), antinuclear antibody (ANA), anticardiolipin antibody (ACA) IgG and IgM, Beta 2 GP IgG and IgM, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and ANA profile with fluctuating PT and APTT results, weak positive LA, indeterminate ACA IgG, fast ESR, increased CRP, ANA profile (++) Ro-52 recombinant.Discussion: Raynaud’s syndrome is a group of symptoms caused by vasospasm and is often associated with autoimmune diseases. The patient presented with typical complaints of Raynaud’s phenomenon and laboratory results of the ANA profile that support a diagnosis of Sjogren’s syndrome. Fluctuations in PT and APTT may be due to intravenous heparin therapy, warfarin, inflammatory conditions, or antiphospholipid antibodies.Conclusion: ANA profile results in patients corresponding to Sjogren’s syndrome, which underlies Raynaud’s syndrome. It is advisable to check mixing studies, liver synthesis function, and antiphospholipid antibodies with an interval of 12 weeks to look for other causes of prolonged PT and APTT.